Legal Protection of Women Forced to Married In Islamic Law and Human Rights Perspective - Anwar Hafidzi; Rina Septiani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine the legal protection of women who are forced to marry according to Islamic law and human rights. The method used in this research is descriptive qualitative with a normative legal approach, namely by analyzing the problem through data from the legal literature. The results of the research found that the marriage law in Indonesia does not recognize the right to consent, on the contrary, the law requires the consent of both parties to enter into a marriage with pleasure without coercion. This is based on the Law of the Republic of Indonesia Number 39 of 1999 concerning Human Rights and Marriage Law Number 1 of 1974. Once the reinterpretation of the right to ijbar is considered objective because this concept is based on the form of protection and responsibility in choosing one's life partner.